Assessment of technical and financial challenges for renewable energy project alternatives - Eti, Serkan; Yüksel, Serhat; Dinçer, Hasan; Kalkavan, Hakan; Hacıoğlu, Ümit; Mikhaylov, Alexey; Shah Danish, Mir Sayed; Pinter, Gabor (Elsevier Ltd., 2024)
The purpose of this study is to assess technical and financial challenges for renewable energy project alternatives with a novel model. Firstly, a set of technical and financial challenges is created by considering the results of the literature evaluation. After that, the weights of these values are computed by Sine Trigonometric Pythagorean Fuzzy (ST-PFN) DEMATEL. The next step includes the ranking of six renewable energy alternatives with interval valued Spherical fuzzy multicriteria analysis with ratio and categorical data (SF MAIRCA) approach. Entropy and ARAS methodology are also considered to make comparative evaluation. Similarly, sensitivity analysis is also conducted for 10 different cases. It is concluded that the analysis results of all methods are the same. Therefore, it is identified that the findings of the proposed model are reliable and coherent. Identification of the most crucial technical and financial challenges of the renewable energy projects is the most important contribution of this manuscript. Furthermore, preferring the sine trigonometric structure in the proposed model will provide superiority to this model in many respects. It is concluded that difficulty in accessing finance for local projects is the most significant challenge for renewable energy investments. Moreover, competitive pricing of renewable sources is another critical issue in this regard. Additionally, it is identified that solar is the most successful renewable energy alternative to overcome technical and financial challenges.
Keywords: Energy Investments; Financial Challenges; Renewable Energy; Technical Improvement